The Stain of the Original Salt: Red Heats on Chrome Tanned Leathers and Purple Spots on Ancient Parchments Are Two Sides of the Same Ecological Coin - Perini, Nicoletta; Mercuri, Fulvio; Thaller, Maria Cristina; Orlanducci, Silvia; Castiello, Domenico; Talarico, Valerio; Migliore, Luciana (Frontiers in Microbiology, 2019)
Animal hides are one of man’s earliest and mostly used material; many rawhide products, primarily leather, are used for several purposes since centuries. The peculiar mechanical properties of leather made it material of choice for many different applications and goods; consequently, leather industry had a great success in all human cultures. Unfortunately, due to their animal origin, rawhides may undergo microbial attack and biodeterioration; but in the centuries, different processes and treatments (brining, vegetal or chrome tanning, tawing, etc.) were set up to face the biological attack and modify/stabilize the hide mechanical properties. Nevertheless, even present-day rawhides are subjected to biological colonization and traces of this colonization are clearly shown in chrome tanned leathers (in the wet blue stage), with obvious economic damages; tanned leathers often show isolated or coalescent red patches, known as red heat deterioration. Even parchments, hide product which derive from another manufacturing procedure, undergo microbial attack and biodeterioration. A frequent ancient parchment alteration, called purple spots, show signs of biodeterioration comparable to the red heat deterioration. Recently, an ecological succession model explained the process of historical parchment purple spot deterioration, suggesting the haloarchaea H. salinarum as the triggering pioneer organism of this biological attack; salting of hides – to prevent the hide from rotting – has been identified as the responsible for haloarchaeal colonization (Migliore et al., 2019). The aim of this study was to investigate the dynamics of biodeterioration on chrome tanned leathers and its effects on the stability/integrity of collagen structure. To this end, standard cultivation methods were integrated with three updated technologies, including Next Generation Sequencing, RAMAN spectroscopy and Light Transmitted Analysis. Moreover, to evaluate if leather and parchment share common culprits and effects of the biodeterioration, a comparison between chrome tanned leather vs historical parchments was performed, as regard both the colonizing microorganisms and effects on the physical properties of the hide product.